Managing bite wounds in male a Mona monkey (cercopithecus mona) (2012)
This paper reports on the management of bite wounds inflicted on an adult male mona monkey by two other males in an attempt to mate the only female in the group. The deep laceration wounds which were at the left cranial thoracic and left caudal abdominal walls, the lateral aspect of the right thigh, the planter surface of the right fore limb and the right triceps muscle were managed with honey incorporated bandage dressings and delayed primary closure with sutures. The unique wound management procedure especially in wild life species,as well as the need to prevent group fight among wild life species in captivity especially mona monkeys through understanding of their social interactive structure formed the objectives of this report. Information acquisition by Zoo Veterinarians and managers, on social interaction among wild life species could help in preventing injuries, reducing cost of zoo animal keeping and conserving the few wild species presently available in our zoological gardens and game reserves